City metaphor in the context of wisdom and civilization - Kayadibi, Saim (International Institute of Islamic Thought and Civilization (ISTAC), 2016)
In today's globalized societies, original, unaffected ideas have lost their influence because with technological developments, almost the whole world can be seen as a single city. Yet in urban culture, the understanding of living together, leaves its place in a smaller community and even more to individualism. While wisdom and civilization are integrated perception of the city, in the course of time this perception has been transformed, shaping the mentality not where it is viewed from, however, but from how it is viewed. In this context, the city concept through this perception requires further discussion. No civilization can be discussed from a place where a city does not exist. However, now the concept has been transformed into an understanding that wisdom and civilization cannot be discussed from a place where there are no universities. With regards to this, universities become centres for Islamic civilization to grow and flourish like cities before. It discusses neither wisdom and civilization nor law and jurisprudence in places where there are no social communities. Therefore, in this paper, wisdom and civilization will be considered in line with the transformation of the city metaphor.